Artificial fine aggregate based on high-chloride-content sludge and method for preparing the same

CN123003173APending Publication Date: 2026-10-30CHINA CONSTRUCTION SIXTH ENGINEERING DIVISION CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611489499.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]将污泥制备为建筑材料时,污泥中的水分和细颗粒容易造成物料黏结、团聚和造粒不稳定,其中的可溶性氯离子还可能在后续使用过程中释放,影响水泥基材料的耐久性

Benefits of technology

(1)通过铝镁水滑石和沸石粉对污泥中部分可迁移离子进行吸附或交换,有利于减少氯离子和部分重金属的迁移;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003173A_ABST
    Figure CN123003173A_ABST
Patent Text Reader

Abstract

The present application relates to solid waste resource utilization and building material technical field, disclose a kind of artificial fine aggregate based on high chloride ion content sludge and its preparation method.The present application first mixes silica fume, slag powder, sulphoaluminate cement, metakaolin, aluminium magnesium hydrotalcite, zeolite powder and phosphate rock powder, then mixes with screened sludge, adds composite alkaline solution twice, and is prepared by high shear wet mixing granulation, in-machine standing and curing artificial fine aggregate, and the water-soluble chloride ion content of the artificial fine aggregate is less than 0.1%.Through the synergistic effect of cementing material, adsorbent material, phosphorus-based material and composite alkaline solution, the water-soluble chloride ion release in the obtained artificial fine aggregate is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of solid waste resource utilization and building materials technology, and in particular to an artificial fine aggregate based on sludge with high chloride ion content and its preparation method. Background Technology

[0002] Urban sewage sludge typically has a high water content and contains fine particles, organic matter, soluble salts, and a certain amount of heavy metals. In coastal cities, the chloride ion content in sludge from waterways and drainage channels may be significantly higher than in ordinary urban sewage sludge. Improper disposal can easily lead to odor, secondary pollution, and land occupation. Preparing sludge into building materials is one way to utilize sludge resources.

[0003] When sludge is used to prepare building materials, the moisture and fine particles in the sludge can easily cause material adhesion, agglomeration, and unstable granulation. Soluble chloride ions may also be released during subsequent use, affecting the durability of cement-based materials. Existing sludge solidification and granulation methods typically use cement, mineral admixtures, or alkaline activating components. However, for sludge with both high moisture content and high chloride ion content, problems such as difficulty in granulation, insufficient particle strength, high water absorption, and significant release of water-soluble chloride ions remain.

[0004] Therefore, it is necessary to provide an artificial fine aggregate and its preparation method that can adapt to the above-mentioned characteristics of sludge raw materials and reduce the release of water-soluble chloride ions. Summary of the Invention

[0005] In view of this, in order to solve the above problems, the present invention provides an artificial fine aggregate based on sludge with high chloride ion content and its preparation method. Through the synergistic effect of cementitious materials, adsorbent materials, phosphorus-based materials and composite alkaline solutions, the release of water-soluble chloride ions in the obtained artificial fine aggregate is reduced.

[0006] The technical solution of this invention is implemented as follows: This invention provides a method for preparing artificial fine aggregate based on sludge with high chloride ion content, comprising the following steps: S1. Mix silica fume, slag powder, sulfoaluminate cement, metakaolin, aluminum magnesium hydrotalcite, zeolite powder and phosphate rock powder evenly to form a dry material. S2. Mix the sludge with the dry material to form a mixed powder; S3. Add a portion of the composite alkaline solution to the mixed powder and stir for 3-5 minutes to form a plastic slurry; S4. The plastic slurry is fed into a high-shear wet mixing granulator and stirred at a stirring paddle speed of 180-220 rpm and a cutting granulator speed of 1300-1700 rpm. The remaining composite alkaline solution is sprayed in through a side wall nozzle and the remaining composite alkaline solution is sprayed out within 3-5 minutes. Then, the stirring paddle speed is increased to 350-450 rpm and the cutting granulator speed is increased to 2500-3000 rpm, and granulation is carried out for 5-8 minutes. After turning off the granulator, the granules are allowed to stand in the machine for 10-15 minutes to obtain shaped granules. S5. The shaped particles are cured for 28 days at a temperature of 20±2℃ and a relative humidity of not less than 70% to obtain artificial fine aggregate. The sludge has a water-soluble chloride ion content of 1%-2%, a moisture content of 25%-40%, and a maximum particle size of no more than 3.35 mm.

[0007] This invention utilizes a composite alkaline solution to activate water in sludge, which then reacts with slag powder, sulfoaluminate cement, metakaolin, and silica fume gel to ultimately form artificial fine aggregate with a certain strength. By adding the composite alkaline solution in two parts, both the formation of plastic sludge and particle growth during the granulation process are considered, which helps improve particle density and granulation stability.

[0008] After shutting down the high-speed shear mixing granulator, the material is not discharged immediately. The rapid setting characteristics of the rapid-hardening sulfoaluminate cement allow the artificial fine aggregate to establish initial skeleton strength, reducing the possibility of deformation after discharge.

[0009] In some embodiments, the mass ratio of the portion of the composite alkaline solution added in step S3 to the remaining composite alkaline solution added in step S4 is 3:7-7:3.

[0010] In some embodiments, the composite alkaline solution is prepared by mixing sodium silicate, an aqueous solution of sodium hydroxide, and sodium methylsilicate.

[0011] In some embodiments, the composite alkaline solution comprises, by mass percentage, 72%-80% sodium silicate, 15%-20% sodium hydroxide aqueous solution, and 5%-8% sodium methylsilicate; the modulus of the sodium silicate is 1-2, and the mass concentration of the sodium hydroxide aqueous solution is 30%-40%.

[0012] In some embodiments, the raw materials for preparing the artificial fine aggregate, by weight, include: 48-57 parts sludge, 2-4 parts silica fume, 5-10 parts slag powder, 10-15 parts sulfoaluminate cement, 4-7 parts metakaolin, 0.5-2 parts aluminum-magnesium hydrotalcite, 5.5-9.5 parts composite alkaline solution, 2-5 parts zeolite powder, and 3-7 parts phosphate rock powder.

[0013] In some embodiments, in step S1, the sulfoaluminate cement is 42.5 rapid-hardening sulfoaluminate cement, and the slag powder is S95 grade slag powder.

[0014] In some embodiments, in step S1, the particle size of the metakaolin is 0-20 μm, the particle size of the zeolite powder is 0-75 μm, and the particle size of the aluminum-magnesium hydrotalcite is 0-5 μm.

[0015] In some embodiments, in step S1, the particle size of the silica fume is 0-1 μm.

[0016] In some embodiments, the phosphate rock powder is ball-milled before being added in step S1 for 2-4 hours, and the maximum particle size of the resulting phosphate rock powder is no greater than 5 μm.

[0017] The present invention also provides an artificial fine aggregate based on sludge with high chloride ion content, wherein the water-soluble chloride ion content of the artificial fine aggregate is less than 0.1%.

[0018] Compared with methods that use only sludge and conventional cement for solidification and granulation, the advantages of this invention are as follows: (1) By adsorbing or exchanging some of the migratable ions in the sludge with aluminum-magnesium hydrotalcite and zeolite powder, it is beneficial to reduce the migration of chloride ions and some heavy metals. (2) Phosphorus-containing mineral components are provided by phosphate rock powder and participate in the solidification process in an alkaline and calcareous cementitious environment, which is conducive to further reducing the release of water-soluble chloride ions, so that the water-soluble chloride ion content, water absorption rate and leaching concentration of some heavy metals of the obtained artificial fine aggregate are lower than those of the corresponding comparative proportion. (3) The cementitious skeleton formed by sulfoaluminate cement, slag powder, metakaolin and silica fume is beneficial to improving the structural integrity of the molded particles; (4) By adding the composite alkaline solution in two parts, the formation of plastic mud and particle growth during the granulation process are taken into account, which is beneficial to improving particle density and granulation stability. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a flowchart of a method for preparing artificial fine aggregate based on sludge with high chloride ion content according to the present invention. Figure 2This is a physical image of an artificial fine aggregate based on sludge with high chloride ion content obtained by the present invention. Figure 3 The sludge with high chloride ion content used in the drainage channels of the central urban area of ​​Tianjin used in the embodiments and comparative examples of this invention; Figure 4 This is a particle crushing strength curve of an artificial fine aggregate particle in the artificial fine aggregate of Embodiment 1 of the present invention. Figure 5 This is a particle crushing strength curve of a single artificial fine aggregate particle in the artificial fine aggregate of Comparative Example 1 of the present invention. Figure 6 This is a particle crushing strength curve of a single artificial fine aggregate particle in Comparative Example 2 of the present invention. Figure 7 This is a particle crushing strength curve of a single artificial fine aggregate particle in the artificial fine aggregate of Comparative Example 3 of the present invention. Figure 8 This is a particle crushing strength curve of a single artificial fine aggregate particle in Comparative Example 4 of the present invention. Figure 9 This is a particle crushing strength curve of a single artificial fine aggregate particle in the artificial fine aggregate of Comparative Example 5 of the present invention. Figure 10 This is a particle crushing strength curve of a single artificial fine aggregate particle in Comparative Example 6 of the present invention. Figure 11 This is a particle crushing strength curve of a single artificial fine aggregate particle in Comparative Example 7 of the present invention. Detailed Implementation

[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0022] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.

[0023] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0024] I. Raw Materials and Equipment Description Except for explicitly stated single variables, the preparation processes of all examples and comparative examples are completely consistent in terms of raw material specifications, equipment models, and basic process parameters to ensure that the experimental data are parallel and reproducible. Unless otherwise specified, the raw materials and equipment used in the following examples and comparative examples are all commercially available conventional raw materials and commercially available conventional equipment.

[0025] The sludge used in this embodiment was taken from drainage channels in the central urban area of ​​Tianjin. Before use, the sludge was sieved through a 6-mesh screen to remove shells, stones, and other visible coarse impurities. The moisture content of the sludge after sieving was 25%-40%, the water-soluble chloride ion content was 1%-2%, and the maximum particle size was no greater than 3.35 mm. A picture of the actual sludge used is shown below. Figure 3 As shown, its water content is 40%, and its water-soluble chloride ion content is 2%.

[0026] In this invention, the water-soluble chloride ion content and moisture content of the sludge are measured based on the sludge after sieving. Unless otherwise stated, the sludge mass in the formula and preparation method refers to the mass of wet sludge after sieving.

[0027] The sulfoaluminate cement is 42.5 rapid-hardening sulfoaluminate cement; the slag powder is S95 grade slag powder; the maximum particle size of metakaolin is no more than 20μm; the maximum particle size of zeolite powder is no more than 75μm; the maximum particle size of aluminum-magnesium hydrotalcite is no more than 5μm; and the maximum particle size of silica fume is no more than 1μm.

[0028] The phosphate rock powder used is ball-milled phosphate rock powder. Before being added, the phosphate rock powder is ball-milled in a planetary ball mill for 3 hours to obtain phosphate rock powder with a maximum particle size of no more than 5 μm.

[0029] The sodium hydroxide aqueous solution has a mass concentration of 30%. The sodium silicate is liquid sodium silicate with a modulus of 2, and the methylsilicate is liquid.

[0030] The high-shear wet mixing granulator uses commercially available equipment, specifically the high-shear wet mixing granulator (GHL high-speed wet mixing granulator) produced by Changzhou Yibu Drying Equipment Co., Ltd.

[0031] II. Specific Preparation Method Preparation of compound alkaline solution A composite alkaline solution was prepared by mixing sodium silicate, sodium hydroxide aqueous solution, and sodium methylsilicate. The total mass of the composite alkaline solution was 100%, and the total mass percentage of each component was 100%.

[0032] The sodium silicate has a mass percentage of 72%-80%, the sodium hydroxide aqueous solution has a mass percentage of 15%-20%, and the methylsilicate has a mass percentage of 5%-8%. The modulus of sodium silicate is 2, and the mass concentration of the sodium hydroxide aqueous solution is 30%.

[0033] Preparation of artificial fine aggregate Reference Figure 1 The preparation method of artificial fine aggregate is as follows: S1. Mix silica fume, slag powder, sulfoaluminate cement, metakaolin, aluminum magnesium hydrotalcite, zeolite powder and phosphate rock powder evenly to obtain dry material; S2. Mix the sludge with the dry material to obtain a mixed powder. S3. Add a portion of the composite alkaline solution to the mixed powder and stir for 3-5 minutes to form a plastic mud. S4. Add the plastic slurry to a high-shear wet mixing granulator and premix it with the agitator at 180-220 rpm and the granulator blade at 1300-1700 rpm. At the same time, add the remaining compound alkaline solution through the side wall nozzle and complete the addition within 3-5 minutes. Then, increase the agitator speed to 350-450 rpm and the granulator blade speed to 2500-3000 rpm, and continue granulation for 5-8 minutes. Turn off the granulator and let the granules stand in the machine for 10-15 minutes to obtain shaped granules. S5. The molded particles are cured for 28 days at a temperature of 20±2℃ and a relative humidity of not less than 70% to obtain artificial fine aggregate.

[0034] The mass ratio of the portion of the composite alkaline solution added in step S3 to the remaining composite alkaline solution added in step S4 is 3:7-7:3.

[0035] The actual image of the artificial fine aggregate prepared using this method is shown below. Figure 2 As shown, it needs to be passed through a 4-mesh sieve before use to ensure that the particle size of the artificial fine aggregate is no greater than 4.75mm.

[0036] III. Performance Testing Methods (1) Test method for crushing strength of artificial fine aggregate particles: The artificial fine aggregate is sieved, and particles between 7 mesh and 8 mesh are selected. A single particle is placed on the loading platform of a universal testing machine, and vertical pressure is slowly applied. The maximum pressure value when the particle begins to break is recorded. At least 3 particles are measured in each group, and the arithmetic mean is taken as the crushing strength of the particles in that group. The standard deviation is also recorded.

[0037] (2) Method for testing the water absorption rate of artificial fine aggregate particles: The test is conducted according to ASTM C128-25, "Standard Test Method for Relative Density (Specific Gravity) and Water Absorption Rate of Fine Aggregates". Take about 1 kg of sample and dry it to constant weight at 110±5℃, and record the dried mass as m0. Immerse the sample in distilled water at 23±2℃, with the water level about 20 mm above the sample, and let it stand for 24±4 h. Take out the sample, remove the water adhering to the surface of the particles, and weigh the saturated surface dry mass m1. Then dry the sample again to constant weight, and confirm that the mass is consistent with m0 or within the specified error range. The water absorption rate is calculated according to the following formula: W=(m1-m0) / m0×100%. At least 3 parallel determinations are performed for each group, the arithmetic mean is taken, and the standard deviation of the parallel determinations is recorded.

[0038] (3) Leaching toxicity test method using sulfuric acid and nitric acid: The test was conducted according to the "Leaching Toxicity of Solid Waste - Sulfuric Acid and Nitric Acid Method" (HJ / T299-2007). First, 200g of artificial fine aggregate was weighed and placed in a container. Second, concentrated sulfuric acid and concentrated nitric acid were mixed at a mass ratio of 2:1 and diluted with water to adjust the pH to approximately 3.2. This mixed solution is the extractant. Then, 2L of extractant was added at a liquid-to-solid ratio of 10:1 (L / kg). After tightening the cap, the container was fixed on a tilting shaker and continuously rotated at a frequency of 30r / min at 23±2 degrees Celsius for 18 hours. During this period, the gas pressure in the bottle needed to be released periodically. After the shaking was completed, the container was allowed to stand for 16 hours. Finally, the extract in the container was filtered using a vacuum filter and the filtrate was collected. Before testing, the filtrate needs to be digested. Specifically, 50 mL of the leachate is measured into a PTFE crucible, 5 mL of concentrated nitric acid is added, and the mixture is heated on a 180°C hot plate for 1-2 hours. The resulting solution is then transferred to a sample tube for testing. Toxic heavy metals in the leachate sample are tested using ICP-OES. This method is based on inductively coupled plasma at high temperatures, where elements in the sample undergo sequential evaporation, atomization, excitation, and ionization. By detecting the characteristic emission spectra, the concentration of the analyte can be accurately determined. This experiment used an ICP spectrometer manufactured by Platinum Elmer, Inc.

[0039] (4) Method for detecting water-soluble chloride ion content: The test was conducted in accordance with the Technical Specification for Detection of Chloride Ion Content in Concrete (JGJ / T 322-2013). 10g of artificial fine aggregate particles and 100mL of deionized water were added to a beaker, and the mixture was stirred and extracted for 5min at a stirring speed of 500rpm to obtain a suspension. The suspension was filtered through filter paper for solid-liquid separation to obtain a filtrate. The filtrate was acidified with dilute nitric acid to make it weakly acidic, resulting in a weakly acidic filtrate. Silver nitrate solution was used as the titrant to titrate the chloride ions in the weakly acidic filtrate to determine the chloride ion content. The chloride ion concentration of the weakly acidic filtrate was calculated based on the concentration and consumption of the silver nitrate solution used in the titration, and the content of free chloride ions in the artificial fine aggregate particles was further calculated.

[0040] Each group should be tested in at least three parallel trials, and the mean and standard deviation should be recorded. This result represents the water-soluble chloride ion content, and is not equivalent to the total chloride content in the artificial fine aggregate.

[0041] IV. Implementation Examples and Comparative Examples Example 1 The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 48 parts sludge, 2 parts silica fume, 5 parts slag powder, 10 parts 42.5 rapid hardening sulfoaluminate cement, 4 parts metakaolin, 0.5 parts aluminum magnesium hydrotalcite, 5.5 parts composite alkaline solution, 2 parts zeolite powder, and 3 parts phosphate rock powder.

[0042] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 75%, sodium hydroxide aqueous solution 20%, and sodium methylsilicate 5%.

[0043] The preparation method includes the following steps: S1. Mix silica fume, slag powder, sulfoaluminate cement, metakaolin, aluminum magnesium hydrotalcite, zeolite powder and phosphate rock powder evenly to obtain dry material; S2. Mix the sludge with the dry material to obtain a mixed powder. S3. Add a portion of the composite alkaline solution to the mixed powder and stir for 5 minutes to form a plastic mud. S4. Add the plastic slurry to a high-shear wet mixing granulator and premix it with a stirring paddle at 220 rpm and a cutting granulator at 1700 rpm. At the same time, add the remaining composite alkaline solution through the side wall nozzle and complete the addition within 5 minutes. Then, increase the stirring paddle speed to 450 rpm and the cutting granulator speed to 3000 rpm, and continue granulation for 8 minutes. Turn off the granulator and let the granules stand in the machine for 15 minutes to obtain shaped granules. S5. The molded particles are cured for 28 days at a temperature of 22℃ and a relative humidity of not less than 70% to obtain artificial fine aggregate.

[0044] In step S3, the mass ratio of the partial composite alkaline solution to the remaining composite alkaline solution in step S4 is 3:7. The composite alkaline solution is prepared by mixing sodium silicate, an aqueous solution of sodium hydroxide, and sodium methylsilicate.

[0045] Example 2 The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 57 parts sludge, 4 parts silica fume, 10 parts slag powder, 15 parts 42.5 rapid hardening sulfoaluminate cement, 7 parts metakaolin, 2 parts aluminum magnesium hydrotalcite, 9.5 parts composite alkaline solution, 5 parts zeolite powder, and 7 parts phosphate rock powder.

[0046] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 80%, sodium hydroxide aqueous solution 15%, and sodium methylsilicate 5%.

[0047] The preparation method includes the following steps: S1. Mix silica fume, slag powder, sulfoaluminate cement, metakaolin, aluminum magnesium hydrotalcite, zeolite powder and phosphate rock powder evenly to obtain dry material; S2. Mix the sludge with the dry material to obtain a mixed powder. S3. Add a portion of the composite alkaline solution to the mixed powder and stir for 3 minutes to form a plastic mud. S4. Add the plastic slurry to a high-shear wet mixing granulator and premix it with a stirring paddle at 180 rpm and a cutting granulator at 1300 rpm. At the same time, add the remaining composite alkaline solution through the side wall nozzle and complete the addition within 3 minutes. Then, increase the stirring paddle speed to 350 rpm and the cutting granulator speed to 2500 rpm, and continue granulation for 5 minutes. Turn off the granulator and let the granules stand in the machine for 10 minutes to obtain shaped granules. S5. The molded particles are cured for 28 days at a temperature of 20℃ and a relative humidity of not less than 70% to obtain artificial fine aggregate.

[0048] The mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 is 7:3.

[0049] Example 3 The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 52.5 parts sludge, 3 parts silica fume, 7.5 parts slag powder, 12.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 1.25 parts aluminum magnesium hydrotalcite, 7.5 parts composite alkaline solution, 3.5 parts zeolite powder, and 6.75 parts phosphate rock powder.

[0050] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 75%, sodium hydroxide aqueous solution 17.5%, and sodium methylsilicate 7.5%.

[0051] The preparation method of artificial fine aggregate is as follows: S1. Mix silica fume, slag powder, 42.5 rapid hardening sulfoaluminate cement, metakaolin, aluminum magnesium hydrotalcite, zeolite powder, and phosphate rock powder evenly to form a dry material. S2. Mix the sludge with dry materials to form a mixed powder; S3. Add a portion of the composite alkaline solution to the mixed powder and stir for 4 minutes to form a plastic slurry; S4. Put the plastic mud into the high-shear wet mixing granulator. The stirring paddle speed is 200 rpm and the cutting granulator speed is 1500 rpm. The remaining composite alkaline solution is sprayed in through the side wall nozzle. The remaining composite alkaline solution is sprayed in within 4 minutes. Then the stirring paddle speed is increased to 400 rpm and the cutting granulator speed is increased to 2700 rpm for granulation. After 7 minutes, the high-speed shear mixing granulator is turned off and the granules are allowed to stand in the machine for 13 minutes to form shaped granules. S5. Place the molded particles under conditions of 18℃ and relative humidity not less than 70% for 28 days to form artificial fine aggregate.

[0052] The mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 is 5:5.

[0053] Example 4 The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 51 parts sludge, 3.5 parts silica fume, 9 parts slag powder, 14 parts 42.5 rapid hardening sulfoaluminate cement, 6 parts metakaolin, 1.5 parts aluminum magnesium hydrotalcite, 8 parts composite alkaline solution, 4 parts zeolite powder, and 3 parts phosphate rock powder.

[0054] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 72%, sodium hydroxide aqueous solution 20%, and sodium methylsilicate 8%.

[0055] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 5:5.

[0056] Example 5 The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 55 parts sludge, 2.5 parts silica fume, 6 parts slag powder, 14 parts 42.5 rapid hardening sulfoaluminate cement, 4.5 parts metakaolin, 1 part aluminum magnesium hydrotalcite, 6.5 parts composite alkaline solution, 3.5 parts zeolite powder, and 7 parts phosphate rock powder.

[0057] The composite alkaline solution, by mass percentage (100%), has the following weight ratio of raw materials: sodium silicate 78%, sodium hydroxide aqueous solution 16%, and sodium methylsilicate 6%.

[0058] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 6:4.

[0059] Example 6 The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 50 parts sludge, 3 parts silica fume, 9 parts slag powder, 11 parts 42.5 rapid hardening sulfoaluminate cement, 6.5 parts metakaolin, 1.8 parts aluminum magnesium hydrotalcite, 9 parts composite alkaline solution, 4.5 parts zeolite powder, and 5.2 parts phosphate rock powder.

[0060] The composite alkaline solution, by mass percentage (100%), has the following weight ratio of raw materials: sodium silicate 73%, sodium hydroxide aqueous solution 19%, and sodium methylsilicate 8%.

[0061] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 4:6.

[0062] Example 7 The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 56 parts sludge, 2 parts silica fume, 6.5 parts slag powder, 14.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 0.8 parts aluminum magnesium hydrotalcite, 6 parts composite alkaline solution, 2 parts zeolite powder, and 6.7 parts phosphate rock powder.

[0063] The composite alkaline solution, by mass percentage (100%), has the following weight ratio of raw materials: sodium silicate 79%, sodium hydroxide aqueous solution 15%, and sodium methylsilicate 6%.

[0064] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 5:5.

[0065] Comparative Example 1 (without aluminum-magnesium hydrotalcite) The weight ratio of the artificial fine aggregate raw materials based on sludge with high chloride ion content is as follows: 52.5 parts sludge, 3 parts silica fume, 7.5 parts slag powder, 12.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 7.5 parts composite alkaline solution, 3.5 parts zeolite powder and 6.75 parts phosphate rock powder.

[0066] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 75%, sodium hydroxide aqueous solution 17.5%, and sodium methylsilicate 7.5%.

[0067] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 5:5.

[0068] Comparative Example 2 (without added phosphate rock powder) The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 52.5 parts sludge, 3 parts silica fume, 7.5 parts slag powder, 12.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 1.25 parts aluminum magnesium hydrotalcite, 7.5 parts composite alkaline solution and 3.5 parts zeolite powder.

[0069] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 75%, sodium hydroxide aqueous solution 17.5%, and sodium methylsilicate 7.5%.

[0070] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 5:5.

[0071] Comparative Example 3 (without zeolite powder) The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 52.5 parts sludge, 3 parts silica fume, 7.5 parts slag powder, 12.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 1.25 parts aluminum magnesium hydrotalcite, 7.5 parts composite alkaline solution and 6.75 parts phosphate rock powder.

[0072] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 75%, sodium hydroxide aqueous solution 17.5%, and sodium methylsilicate 7.5%.

[0073] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 5:5.

[0074] Comparative Example 4 (The phosphate rock powder was unmilled phosphate rock powder with a maximum particle size of 1 mm). The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 52.5 parts sludge, 3 parts silica fume, 7.5 parts slag powder, 12.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 1.25 parts aluminum magnesium hydrotalcite, 7.5 parts composite alkaline solution, 3.5 parts zeolite powder, and 6.75 parts phosphate rock powder.

[0075] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 75%, sodium hydroxide aqueous solution 17.5%, and sodium methylsilicate 7.5%.

[0076] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 5:5.

[0077] Comparative Example 5 (The composite alkaline solution does not contain sodium methylsilicate) The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 52.5 parts sludge, 3 parts silica fume, 7.5 parts slag powder, 12.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 1.25 parts aluminum magnesium hydrotalcite, 7.5 parts composite alkaline solution, 3.5 parts zeolite powder, and 6.75 parts phosphate rock powder.

[0078] The composite alkaline solution, by mass percentage (100%), has the following weight ratio of raw materials: sodium silicate 80%, sodium hydroxide aqueous solution 20%, and sodium methylsilicate 0%.

[0079] Artificial fine aggregate was prepared according to the preparation method of Example 3, wherein the mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 was 5:5.

[0080] Comparative Example 6 (The mass ratio of the partial composite alkaline solution described in step S3 to the remaining composite alkaline solution described in step S4 during the preparation process is 9:1) The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 52.5 parts sludge, 3 parts silica fume, 7.5 parts slag powder, 12.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 1.25 parts aluminum magnesium hydrotalcite, 7.5 parts composite alkaline solution, 3.5 parts zeolite powder, and 6.75 parts phosphate rock powder.

[0081] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 75%, sodium hydroxide aqueous solution 17.5%, and sodium methylsilicate 7.5%.

[0082] The preparation method includes the following steps: S1. Mix silica fume, slag powder, 42.5 rapid hardening sulfoaluminate cement, metakaolin, aluminum magnesium hydrotalcite, zeolite powder, and phosphate rock powder evenly to form a dry material. S2. Pass the sludge through a 6-mesh sieve, and mix the sludge that passes through the sieve with the dry material to form a mixed powder. S3. Add 90% composite alkaline solution to the mixed powder and stir for 4 minutes to form plastic mud; S4. Put the plastic mud into the high-shear wet mixing granulator. The stirring paddle speed is 200 rpm and the cutting granulator speed is 1500 rpm. The remaining 10% of the composite alkaline solution is sprayed in through the side wall nozzle. The remaining composite alkaline solution is sprayed in within 4 minutes. Then the stirring paddle speed is increased to 400 rpm and the cutting granulator speed is increased to 2700 rpm for granulation. After 7 minutes, the high-speed shear mixing granulator is turned off and the granules are allowed to stand in the machine for 13 minutes to form shaped granules. S5. Place the molded particles under conditions of 18℃ and relative humidity not less than 70% for 28 days to form artificial fine aggregate.

[0083] The mass ratio of the partial composite alkaline solution in step S3 to the remaining composite alkaline solution in step S4 is 9:1.

[0084] Comparative Example 7 (Silica fume was directly added to the sludge during the preparation process) The weight ratio of the artificial fine aggregate raw material based on sludge with high chloride ion content is as follows: 52.5 parts sludge, 3 parts silica fume, 7.5 parts slag powder, 12.5 parts 42.5 rapid hardening sulfoaluminate cement, 5.5 parts metakaolin, 1.25 parts aluminum magnesium hydrotalcite, 7.5 parts composite alkaline solution, 3.5 parts zeolite powder, and 6.75 parts phosphate rock powder.

[0085] The composite alkaline solution, by mass percentage (100%), comprises the following raw materials in the following weight ratios: sodium silicate 75%, sodium hydroxide aqueous solution 17.5%, and sodium methylsilicate 7.5%.

[0086] The preparation method includes the following steps: S1. Mix sludge with silica fume, slag powder, 42.5 rapid hardening sulfoaluminate cement, metakaolin, aluminum magnesium hydrotalcite, zeolite powder, and phosphate rock powder evenly to form a mixed powder. S2. Add 50% composite alkaline solution to the mixed powder and stir for 4 minutes to form plastic mud; S3. Put the plastic mud into the high-shear wet mixing granulator. The stirring paddle speed is 200 rpm and the cutting granulator speed is 1500 rpm. The remaining 50% of the composite alkaline solution is sprayed in through the side wall nozzle. The remaining composite alkaline solution is sprayed in within 4 minutes. Then the stirring paddle speed is increased to 400 rpm and the cutting granulator speed is increased to 2700 rpm for granulation. After 7 minutes, the high-speed shear mixing granulator is turned off and the granules are allowed to stand in the machine for 13 minutes to form shaped granules. S4. Place the molded particles under conditions of 18℃ and relative humidity not less than 70% for 28 days to form artificial fine aggregate.

[0087] The mass ratio of the partial composite alkaline solution in step S2 to the remaining composite alkaline solution in step S3 is 5:5.

[0088] V. Results Analysis The formulation ratio and performance testing method were tested according to the above embodiments. Figure 4 This is a particle crushing strength curve of artificial fine aggregate particles according to Embodiment 1 of the present invention. Figure 5-11 This is a particle crushing strength curve of artificial fine aggregate particles in Comparative Examples 1-7 of the present invention.

[0089] The performance test results of the artificial fine aggregate are as follows: Table 1 Performance Test Results

[0090] As can be seen from Table 1, under the raw materials and process conditions used in this application, compared with the corresponding comparative examples, the artificial fine aggregates obtained in the examples exhibit lower water-soluble chloride ion content, lower water absorption rate, or higher particle crushing strength. Comparative Example 1 shows that the absence of aluminum-magnesium hydrotalcite increases the water-soluble chloride ion content and the leaching concentration of some heavy metals, as aluminum-magnesium hydrotalcite may adsorb some chloride ions through interlayer anion exchange. Comparative Example 2 shows that the absence of phosphate rock powder increases the water-soluble chloride ion content. Comparative Example 3 shows that the absence of zeolite powder increases the water absorption rate and the leaching concentration of some heavy metals, as zeolite powder may assist in the fixation of some migratable components through pore adsorption and ion exchange. At the same time, zeolite powder, as a fine particle filler, has water absorption properties, which helps to improve the integrity of the internal structure of the particles and reduce the water absorption rate of the artificial fine aggregates. Comparative Example 4 shows that when using phosphate rock powder with a larger particle size, the water-soluble chloride ion content is higher than that in Example 3. In this invention, sulfoaluminate cement, slag powder, metakaolin, and silica fume form a gelling product under the action of a composite alkaline solution, providing a solidified framework for sludge particles. Phosphate rock powder participates in the solidification process of phosphorus-containing minerals in an alkaline gelling environment, which may help further reduce the water-soluble release of chloride ions. Reducing the phosphate rock powder particle size to within 5 μm further enhances the effect of reducing the water-soluble release of chloride ions.

[0091] Comparative Example 5 shows that the water absorption rate increases without the addition of sodium methylsilicate. Sodium methylsilicate can reduce the water absorption rate.

[0092] Comparative Example 6 shows that when the ratio of the composite alkaline solution is 9:1, the particle crushing strength decreases and the water absorption rate increases. It is speculated that adding the composite alkaline solution in two parts allows the mixed powder to first form a plastic slurry, and then, during the granulation stage, adjusts the liquid phase distribution on the particle surface and inside, thereby improving the particle density and structural integrity after curing. Furthermore, combined with Comparative Example 5, it can be inferred that sodium methylsilicate, as a water-repellent agent, sprayed onto the surface of aggregate particles, can significantly reduce water absorption.

[0093] Comparative Example 7 shows that directly mixing silica fume with sludge affects granulation and particle strength. Due to the high moisture content of the sludge, visual observation shows localized agglomeration and clumping when silica fume is directly added to the sludge. Therefore, this invention first mixes silica fume with other powder raw materials to form a dry material, and then mixes it with sludge to improve powder dispersion.

[0094] The above working principle is an explanation of the possible modes of operation of the present invention, and does not limit the present invention to achieving technical effects only through a specific chemical reaction or the formation of a specific crystal phase.

[0095] This invention provides a high-chloride-content sludge-based artificial fine aggregate and its preparation method. By combining raw material proportioning, powder premixing, stepwise addition of a composite alkaline solution, shearing granulation, and curing conditions, granulable artificial fine aggregate can be obtained under the conditions described in the examples, and its particle strength, water absorption, water-soluble chloride ion content, and leaching performance of some heavy metals can be improved.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing artificial fine aggregate based on sludge with high chloride ion content, characterized in that, Includes the following steps: S1. Mix silica fume, slag powder, sulfoaluminate cement, metakaolin, aluminum magnesium hydrotalcite, zeolite powder and phosphate rock powder evenly to form a dry material. S2. Mix the sludge with the dry material to form a mixed powder; S3. Add a portion of the composite alkaline solution to the mixed powder and stir for 3-5 minutes to form a plastic slurry; S4. The plastic slurry is fed into a high-shear wet mixing granulator and stirred at a stirring paddle speed of 180-220 rpm and a cutting granulator speed of 1300-1700 rpm. The remaining composite alkaline solution is sprayed in through a side wall nozzle and the remaining composite alkaline solution is sprayed out within 3-5 minutes. Then, the stirring paddle speed is increased to 350-450 rpm and the cutting granulator speed is increased to 2500-3000 rpm, and granulation is carried out for 5-8 minutes. After turning off the granulator, the granules are allowed to stand in the machine for 10-15 minutes to obtain shaped granules. S5. The shaped particles are cured for 28 days at a temperature of 20±2℃ and a relative humidity of not less than 70% to obtain artificial fine aggregate. The sludge has a water-soluble chloride ion content of 1%-2%, a moisture content of 25%-40%, and a maximum particle size of no more than 3.35 mm.

2. The method for preparing artificial fine aggregate based on sludge with high chloride ion content as described in claim 1, characterized in that: The mass ratio of the portion of the composite alkaline solution added in step S3 to the remaining composite alkaline solution added in step S4 is 3:7-7:

3.

3. The method for preparing artificial fine aggregate based on sludge with high chloride ion content as described in claim 1, characterized in that: The composite alkaline solution is prepared by mixing sodium silicate, sodium hydroxide aqueous solution and sodium methylsilicate.

4. The method for preparing artificial fine aggregate based on sludge with high chloride ion content as described in claim 3, characterized in that: The composite alkaline solution comprises, by mass percentage (100%): 72%-80% sodium silicate, 15%-20% sodium hydroxide aqueous solution, and 5%-8% sodium methylsilicate; the modulus of the sodium silicate is 1-2, and the mass concentration of the sodium hydroxide aqueous solution is 30%-40%.

5. The method for preparing artificial fine aggregate based on sludge with high chloride ion content as described in claim 1, characterized in that, The raw materials for preparing the artificial fine aggregate, by weight, include: 48-57 parts of sludge; 2-4 parts silica fume; 5-10 parts of slag powder; 10-15 parts of sulfoaluminate cement; Parts 4-7 of metakaolin; 0.5-2 parts of aluminum-magnesium hydrotalcite; 5.5-9.5 parts of compound alkaline solution; 2-5 parts zeolite powder; And 3-7 parts of phosphate rock powder.

6. The method for preparing artificial fine aggregate based on sludge with high chloride ion content as described in claim 1, characterized in that: In step S1, the sulfoaluminate cement is 42.5 rapid-hardening sulfoaluminate cement, and the slag powder is S95 grade slag powder.

7. The method for preparing artificial fine aggregate based on sludge with high chloride ion content as described in claim 1, characterized in that: In step S1, the particle size of the metakaolin is 0-20 μm, the particle size of the zeolite powder is 0-75 μm, and the particle size of the aluminum-magnesium hydrotalcite is 0-5 μm.

8. The method for preparing artificial fine aggregate based on sludge with high chloride ion content as described in claim 1, characterized in that: In step S1, the particle size of the silica fume is 0-1 μm.

9. The method for preparing artificial fine aggregate based on sludge with high chloride ion content as described in claim 1, characterized in that: The phosphate rock powder is ball-milled before being added in step S1 for 2-4 hours, and the maximum particle size of the resulting phosphate rock powder is no greater than 5 μm.

10. An artificial fine aggregate based on sludge with high chloride ion content, prepared by the preparation method according to any one of claims 1-9, characterized in that, The water-soluble chloride ion content of the artificial fine aggregate is less than 0.1%.